Manajemen â€œGerakan Literasi Sekolahâ€ Untuk Meningkatkan Minat Baca Pasca Pandemi (Studi Kasus Di Sdit Al-Bayyinah Garut) - Latifah, Hanny; Fatonah, Nurul (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to describe the literacy strengthening program at SDIT Al Bayyinah, especially after the COVID-19 pandemic which made students almost 2 years old have to carry out distance/online learning activities. The research method used a qualitative descriptive method, namely to get a complete and detailed relation to the implementation of the literacy program at SDIT Al Bayyinah. Data collection techniques through interviews, observation and documentation. The results showed that the pandemic did not stop literacy activities at SDIT Al Bayyinah, various activities continued to be carried out during the pandemic including Readathon activities, literacy trees, making poetry, short stories, and other essays in an effort to continue to grow students' literacy skills in various situations and even managed to win the Garut district level literacy competition during the Pandemic and were actively involved in solving the challenges of the Gerakan Literasi Nasional â€œGLN Gareulis Jabar Movement program which had been running for 1.5 years. This literacy activity at SDIT Al Bayyinah is not only carried out by students but also involves teachers and parents.